Antimony mobility during the early stages of stibnite weathering in tailings at the Beaver Brook Sb deposit, Newfoundland. (April 2020) - Borčinová Radková, Anežka; Jamieson, Heather E.; Campbell, Kate M.
Abstract: The aqueous speciation and mineralogy of antimony (Sb) in waters and tailings at Beaver Brook antimony deposit have been analyzed to understand Sb mobility during the initial stages of stibnite (Sb2 S3 ) weathering in a near-surface environment. Dissolution of stibnite in oxidizing conditions releases Sb in drainage water and Sb is incorporated into the mineral structures of several secondary minerals. The most abundant Sb host in Beaver Brook tailings is primary stibnite, which dissolves, releasing Sb(III) to the pore water which rapidly oxidizes to Sb(V). The maximum concentration of Sb in tailings pore water is 26.4 mg/L and only 0.9% is in the form of Sb(III). In all surface water, Sb concentration ranges from 0.01 to 26.1 mg/L (average 9.4 mg/L) and is mostly present in its Sb(V) form (98.9–99.2% of total Sb). The secondary minerals containing Sb formed in tailings impoundment include tripuhyite-like Sb–Fe oxides (FeSbO4 ) where Sb is an important part of their structure, with variable Fe/Sb ratios and Sb concentrations of up to 37.8% by weight (average of 21.7%). These are important Sb host phases in the top 30 cm of tailings. Iron oxides enriched in Sb, such as goethite (FeOOH), where Sb (average of 3.9% by weight) is adsorbed or incorporated in the structure are common but represent less than 1.3% of the total mass of Sb. The elevated Mg concentrations in tailing ponds and pore water promote the precipitation of brandholzite (Mg[Sb(OH)6 ]2 ·6H2 O) (in association with gypsum) during dry periods, which is easily dissolved during rainy periods. Brandholzite dissolution may significantly contribute to the concentration of dissolved Sb, together with stibnite dissolution, whereas Sb–Fe oxides are stable in the neutral pH, oxidized surface environment. Arsenic (As) accompanies Sb in all media but its behavior differs from that of Sb. The source of As is arsenopyrite, which decomposes more slowly than stibnite. This may be due to the formation of oxidation rims on arsenopyrite grains composed of Fe, As, S, Sb, and Ca which slow the dissolution, whereas no rims are seen on stibnite. Also, despite similar As and Sb concentration in bulk tailings, the concentration of Sb in drainage water is higher than that of As. In pore water, As(III) is the dominant oxidation state of As suggesting that the oxidation of dissolved As is slower than that of Sb. Graphical abstract: Image 1 Highlights: Stibnite oxidizes faster than arsenopyrite which is passivated by Fe oxyhydroxide rims. Antimony in surface and pore waters is mostly present as Sb(V). A Sb–Fe tripuhyite-like mineral and Sb-bearing goethite act as sinks for Sb. The highly soluble secondary brandholzite acts as both a source and a sink for Sb.